2017
DOI: 10.18632/aging.101326
|View full text |Cite
|
Sign up to set email alerts
|

An expression screen for aged-dependent microRNAs identifies miR-30a as a key regulator of aging features in human epidermis

Abstract: The mechanisms affecting epidermal homeostasis during aging remain poorly understood. To identify age-related microRNAs, a class of non-coding RNAs known to play a key role in the regulation of epidermal homeostasis, an exhaustive miRNA expression screen was performed in human keratinocytes from young or elderly subjects. Many microRNAs modulated by aging were identified, including miR-30a, in which both strands were overexpressed in aged cells and epidermal tissue. Stable MiR-30a over-expression strongly impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 47 publications
4
52
0
2
Order By: Relevance
“…For example, miR-625-3p and miR-671-3p showing significant association with maternal age in our study were described also in study of Huan et al as age-associated miRNAs [23]. Moreover, miR-671-3p seems to be differentially expressed between keratinocytes prepared from child skin and aged skin [24]. Similarly, we identified miRNAs indicating association with maternal BMI or weight gain during pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…For example, miR-625-3p and miR-671-3p showing significant association with maternal age in our study were described also in study of Huan et al as age-associated miRNAs [23]. Moreover, miR-671-3p seems to be differentially expressed between keratinocytes prepared from child skin and aged skin [24]. Similarly, we identified miRNAs indicating association with maternal BMI or weight gain during pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…Upregulation of JNK by galectin-7 [19] Increased keratinocyte differentiation with involucrin expression by oleic acid [20] p63, Skp2 and Msi2 Promotion of cell cycle exit in mouse skin [21] miR-574 ↑ p63 As direct targets of iASPP [22] miR-720 ↑ miR-24 ↑ PAK4 Control of actin cable formation [23] miR-23b-3p ↑ TGIF1 Interference in TGF-β/SMAD signaling [24] miR-378b ↑ NKX3.1 [25] miR-30a ↑ LOX, IDH1, AVEN Barrier function defects in aged epidermis [26] miR-184 ↑ Upregulation of cyclin E and p21 cyclin-dependent kinase inhibitor in a SOCE-dependent manner [27] miR-181a ↑ cell differentiation under high calcium or UVA exposure [28,29] miR [33] miRNAs targeted by p63 miR-34a ↑ SIRT6 miR-34a and miR-34c as direct targets of p63 [34,35] miR-34a ↑ KLK4 Induction of a senescent phenotype in keratinocytes [36] ↑: upregulation (increase), ↓: downregulation (decrease).…”
Section: Snai2 and ∆Np63mentioning
confidence: 99%
“…Defective barrier function is related to aged epidermis. Investigation of the role of miRNAs in age-related keratinocyte differentiation and barrier function revealed that the upregulation of miR-30a in human keratinocytes treated with calcium [28] results in impaired keratinocyte differentiation and barrier defects mediated via lysyl oxidase (LOX), isocitrate dehydrogenase 1 (IDH1), and apoptosis and caspase activation inhibitor (AVEN) [26].…”
Section: Epidermal Calcium Gradientsmentioning
confidence: 99%
“…Some researchers constructed a Drosophila model of skin aging and found that the increased expression of the autophagy marker, Atg7, was associated with skin aging [162]. Another study found that exosome miR-30a can regulate the apoptosis of epidermal cells, and its overexpression led to impaired epidermal differentiation by directly targeting AVEN (encodes a caspase inhibitor), IDH1 (encodes isocitrate dehydrogenase, an enzyme of cellular metabolism), and LOX (encodes lysyl oxidase, a regulator of the proliferation/differentiation balance of keratinocytes), inducing severe barrier dysfunction and skin aging [163]. Treatment for skin aging mainly includes oral antioxidant drugs, topical antiaging agents, and photoelectric and acoustic physical technology.…”
Section: Skinmentioning
confidence: 99%